Avaliação da inclusão do farelo de canola em dietas para ruminantes - Hentz, Fernanda (2010)
Eight Texel x Polwarth crossbred wethers (31.1±3.8 kg BW), four with duodenal cannulae were used in a replicated 4x4 Latin square design to evaluate effects of canola meal (44.4% CP, 29.5% NDF and 3.2% EE; DM basis) on intake, whole-tract digestibility, microbial protein synthesis and nitrogen retention. The basal diet consisted of ad libitum access to sudangrass (10% refusals). Treatments were sudangrass only (control), or supplemented with 5, 10, or 15 g/kg BW of concentrate, offered twice daily at 0800 and 1700h. Concentrate was 90% canola meal and 10% finely ground corn. Wethers were adapted to diets for 10 d followed by a 5-d collection period. Forage DMI decreased linearly (P<0.001) as supplement intake increased, and was 26.1% lower in supplemented animals in relation to the control group. Total DMI, which included forage and supplement, increased 30.6% and digestible OM intake increased 41% with supplementation. Supplementation did not affect DM and OM digestibility, while depressed NDF digestibility and improves N digestibility. Microbial protein synthesis and microbial efficiency were not affected by supplementation. Nitrogen retention was markedly higher in supplemented animals (236% higher), and was due mainly to the higher duodenal flow of amino acids. Supplementation with canola meal improves total nutrient supply, however, exerted a negative effect on forage intake and fiber digestibility in wethers.